Applying Agile Concepts from Software Development into the Design of Flood Disaster Management Framework - F.Mat Saad, M.; Abdul Latif, A.; Othman, M.; S.A. MOHD NOOR, M. (International Journal of Engineering and Technology, 2018)
Managing complex environment often requires flexibility in its processes. This is evident in flood management where the factors that determine the success of it is uncertain. A flexible flood management requires an agile frame-work that allows flexibility to respond to any possible event during a disaster. The concept of agile methods used in software development help to provide values that is used as a basis in offering agility in managing flood complexity. These values are observed during field studies of Standard Operating Procedures (SOP) implementation in managing flood impact at selected flood sites in Malaysia.Â This study aim to identify the key values of agility in developing a framework based on the review of agile methods combined with factors identified from study of successful flood management. The developed framework is aligned with uncertainties mitigation by dividing the disaster areas into small sub-areas, improving communication, and empowering on-site response team with clear leadership.Â Â